2006
DOI: 10.1029/2005jb003905
|View full text |Cite
|
Sign up to set email alerts
|

Low‐degree mantle convection with strongly temperature‐ and depth‐dependent viscosity in a three‐dimensional spherical shell

Abstract: [1] A series of numerical simulations of thermal convection of Boussinesq fluid with infinite Prandtl number, with Rayleigh number 10 7 , and with the strongly temperatureand depth-dependent viscosity in a three-dimensional spherical shell is carried out to study the mantle convection of single-plate terrestrial planets like Venus or Mars without an Earth-like plate tectonics. The strongly temperature-dependent viscosity (the viscosity contrast across the shell is ! 10 5 ) makes the convection under stagnant l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 36 publications
0
32
1
Order By: Relevance
“…For instance, for a moderate viscosity contrast, i.e., the sluggish-lid 52 regime, the convection structure can become large-scale (e.g., McNamara and Zhong, 2005; 53 Tackley, 1996b; Yoshida and Kageyama, 2006) whereas convection under the stagnant lid is 54 typically characterized by small-scale convection (Reese et al, 2005;1999). 55…”
mentioning
confidence: 99%
“…For instance, for a moderate viscosity contrast, i.e., the sluggish-lid 52 regime, the convection structure can become large-scale (e.g., McNamara and Zhong, 2005; 53 Tackley, 1996b; Yoshida and Kageyama, 2006) whereas convection under the stagnant lid is 54 typically characterized by small-scale convection (Reese et al, 2005;1999). 55…”
mentioning
confidence: 99%
“…14b). In particular, the mode of convection denoted by the squares in the figure has been considered to be identical to the ST mode in most of the earlier studies [13,20,24,28], although it has been reported from two-dimensional convection models with a moderately wide box [3] that the changes from wide to narrow convection cells with increasing r η do not necessarily coincide with that in vertical flow structures.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…14a, the classification of convective regimes, inferred from the changes in the horizontal length scales of convection cells, obtained by earlier numerical experiments of thermal convection in three-dimensional spherical shells [2,13,18,28,31]. Among the symbols in the figure, the triangles indicate the conditions for a so-called "sluggish-lid" (SL) mode of convection which is characterized by convection cells of large horizontal scales (see Fig.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 2 more Smart Citations